2021
DOI: 10.1038/s41467-020-20661-8
|View full text |Cite
|
Sign up to set email alerts
|

Interface controlled thermal resistances of ultra-thin chalcogenide-based phase change memory devices

Abstract: Phase change memory (PCM) is a rapidly growing technology that not only offers advancements in storage-class memories but also enables in-memory data processing to overcome the von Neumann bottleneck. In PCMs, data storage is driven by thermal excitation. However, there is limited research regarding PCM thermal properties at length scales close to the memory cell dimensions. Our work presents a new paradigm to manage thermal transport in memory cells by manipulating the interfacial thermal resistance between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 71 publications
(88 reference statements)
4
48
0
Order By: Relevance
“…1 d), which could suggest incomplete crystallization or minor damage from sample preparation; similar observations are found in the 20 nm crystalline GSST film. A ~5% thickness reduction is measured upon crystallization in both 20 and 150 nm films indicating densification of GSST after the phase transformation, similar to previous observations in GST 17 , 35 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1 d), which could suggest incomplete crystallization or minor damage from sample preparation; similar observations are found in the 20 nm crystalline GSST film. A ~5% thickness reduction is measured upon crystallization in both 20 and 150 nm films indicating densification of GSST after the phase transformation, similar to previous observations in GST 17 , 35 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…In chalcogenide-based PCMs, thermal excitation can induce reversible solid-state phase transitions between amorphous and crystalline states 13 , 14 . This phase transition is non-volatile and leads to large contrasts in the electrical 15 , optical 16 , and thermal properties 17 . Germanium antimony telluride, Ge−Sb−Te (GST), is the most popular and the most studied chalcogenide-based PCMs due to its phase stability 14 , large property contrast 18 , and fast switching rate 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In the amorphization process of RESET, a large current is applied to heat the phase change layer above the melting temperature while smaller current is required for the crystallization SET. In this regard, innovative methods for structural and material engineering have been demonstrated to reduce the amorphization current [97][98][99][100][101]. You et al suggested a hybrid PCM architecture of TiW/Ge2Sb2Te5 (GST)/ NiO/Ni to control the crystallinity of GST with self-structured Ni filaments [102].…”
Section: Recent Advances In Nonvolatile Memoriesmentioning
confidence: 99%
“…As one of the most promising candidates for next-generation nonvolatile new memories, phase change memory (PCM) has garnered much attention due to its high-speed cell operation, good reliability, and excellent scalability. [1][2][3][4][5][6][7][8] A PCM cell, which exploits the phase transition characteristic of chalcogenide materials, shows a difference in the resistance of roughly two orders between a low resistance state (LRS, crystalline) and a high resistance state (HRS, amorphous). [4] In order to change the LRS to a HRS, high…”
Section: Introductionmentioning
confidence: 99%